O processo de aprendizagem no contexto da prática profissional de controladores de tráfego aéreo - Aires, Flávio dos Santos (2021)
This study aimed to understand the learning process in the context of the professional practice of air traffic controllers, in the light of experiential learning. The demanding regulation of the sector stems from related responsibilities, given that the air traffic controller professional performance is directly related to the safety and efficiency of air transport. In this context, it is considered relevant to analyze how air traffic controllers learn in the context of their professional practice, in view of contributing to the continuing education and training of these professionals. Therefore, this research was guided by the perspective of experiential learning, understanding that the learning process is constituted by individual elements (cognition, emotions and behavior), by collective aspects (social, political, cultural and environmental elements) and, still, integrated with reflection, as it is considered a characteristic that facilitates learning at both the individual and collective levels. Thus, the research is characterized by an exploratory-descriptive qualitative approach. To perform the data collection, the thematic oral history method and the narrative interview technique were used, in which the research subjects were ten air traffic controllers from the Telecommunications and Air Traffic Service Provider Station in Macaé, Rio de Janeiro. The data were interpreted through comprehensive interpretative analysis. It was found that the trajectory of the controller, since entering the air traffic control area, is full of formal education (training course, operational internship (theory and practice), specific courses, periodic theoretical and practical evaluations, and routine simulated practices) throughout the career. It was also found that the learning gained from the experiences in their daily lives – including unwanted situations (air traffic conflicts and occurrences, system and equipment degradation, emergencies and aviation accidents) – contribute significantly to the learning process of controllers, and also that these professionals recognize the importance of the correlation between learning in practice and the theory learned in formal education processes. Finally, it was confirmed that the controllers usually share experiences with peers and superiors both in the work environment, as well as in the external environment of the company through social interactions with co-workers. In view of the presented scenario, there was a strong influence of professional and social experiences for the learning process of air traffic controllers, mediated by reflection, generating constant reviews of the learned terms.